The Role of Perceived Value in Mediating the Effect of Islamic Branding, Online Customer Reviews, and Price on Halal Cosmetic Purchase Decisions among Muslim Consumers in Serang City - Karomah, Karomah; Peristiwo, Hadi; Ferieka, Hendrieta; Suryani, Suryani; Maskuroh, Nihayatul (Universitas KH. Abdul Chalim Mojokerto, 2026)
The growth of the halal cosmetics market in Indonesia is driven by increasing awareness among Muslim consumers of halal aspects, product safety, and quality, as well as by digital information and perceived value in the purchase decision-making process. This study aims to analyze the role of perceived value in mediating the effects of Islamic branding, online customer review, and price on halal cosmetics purchase decisions among Muslim consumers in Serang City. The research employs a quantitative approach, with data collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS application. The results indicate that Islamic branding, online customer reviews, and price have positive and significant effects on halal cosmetics purchase decisions. These three variables also have positive and significant effects on perceived value. Furthermore, perceived value is proven to have a positive and significant effect on purchase decisions and to mediate the influence of Islamic branding, online customer reviews, and price on halal cosmetics purchase decisions. These findings suggest that perceived value plays a strategic role in integrating religious, informational, and economic factors in shaping Muslim consumers’ decisions regarding halal cosmetic products.